Influence of Human Platelet Lysate on Extracellular Matrix Deposition and Cellular Characteristics in Adipose-Derived Stem Cell Sheets - Cheng, Nai-Chen; Tu, Yuan-Kun; Lee, Ning-Hsu; Young, Tai-Horng (Frontiers in Cell and Developmental Biology, 2020)
Adipose-derived stem cell (ASC) is a valuable source of cell therapy. By stimulating extracellular matrix (ECM) secretion, ASC sheets can be fabricated with enhanced regenerative capabilities. In recent years, human platelet lysate (HPL) provides an attractive alternative to fetal bovine serum (FBS) for the ex vivo expansion of ASCs for clinical use. However, the effect of HPL on ASC sheet formation has not been previously determined. In this study, we compared ECM composition and cellular characteristics of ASC sheets cultured in growth medium supplemented with either FBS or HPL. HPL supplement significantly enhanced ASC proliferation without obvious change in the expression pattern of cell surface markers. We found that culturing ASCs with HPL rendered thicker cell sheets with significantly more ECM deposition, including collagen and fibronectin. Proteomic analysis of the FBS or HPL-cultured cell sheets showed diversity in ECM composition. HPL-cultured ASC sheets exhibited upregulation of interleukin-6 and an anti-inflammatory cytokine, C1q/TNF-related protein-3. Conditioned medium of HPL-cultured ASC sheets significantly enhanced fibroblast migration and tube formation of endothelial cells in vitro, while it inhibited the migration of macrophages toward stimulated macrophages in vitro. TGF-β1-stimulated fibroblasts cultured in ASC sheet-conditioned medium showed downregulation of α-SMA and TGF-β1. By adding an anti-hepatocyte growth factor (HGF) neutralizing antibody in conditioned medium, we indicated that an anti-fibrosis effect of HPL-cultured ASC sheets is partially mediated through the increased secretion of HGF. Moreover, chick embryo chorioallantoic membrane assay showed comparable capillary density after applying either FBS or HPL-cultured ASC sheets, both of which were significantly higher than the control. In conclusion, robust ECM formation with altered ECM composition was noted in ASC sheets cultured in HPL-supplemented medium. Their immunomodulatory and pro-angiogenesis capabilities were largely maintained. Our findings paved the way to elucidate the potential of HPL-cultured ASC sheets for clinical application in tissue regeneration.